Aplikasi Create History Stok Barang pada PT. Singa Perkasa Abadi - Budi, Raden George Samuel; Hartati, Ery (MDP Student Conference, 2025)
PT. Singa Perkasa Abadi is a company engaged in the production and sale of iron materials, such as nails, long iron, light steel and barbed wire. Currently, the process of recording the expenditure and entry of goods still uses paper notes, which have the potential to cause errors in recording and calculating stock of goods, and delays in managing stock of goods, and when shipping goods only relying on delivery letters which can cause errors during shipping of goods. This study aims to develop a website-based digitalization solution for stock management in order to reduce errors and loss of recording, increase efficiency and accuracy of recording. By implementing the Iterative development method and using the Laravel and Bootstrap frameworks. The implementation of this system can increase the company's productivity in managing stock of goods more quickly, accurately, and in an organized manner.